Some Fixed-Circle Results with Different Auxiliary Functions. (9th June 2022) - Kaplan, Elif; Mlaiki, Nabil; Taş, Nihal; Haque, Salma; Souayah, Asma Karoui
Abstract : As the generalization of the fixed-point theory, the fixed-circle problems are interesting and notable geometric constructions. In this paper, we prove that some new necessary conditions are investigated for the existence of a fixed circle of a given self-mapping in G -metric spaces. The well-known Braincari and Chatterjea contractive conditions are generalized for proving the uniqueness of obtained theorems. Finally, an application to parametric rectified linear unit activation functions are given to show the importance of studying the fixed-circle problem.